High-quality supplemental protein enhances acute muscle protein synthesis and long-term strength adaptations to resistance training in young and old adults - Pasiakos, S. M.; Howard, E. E. (The Journal of Nutrition, 2021)
Dietary protein ingestion, alone or when consumed after resistance exercise, stimulates muscle protein synthesis (MPS), resulting in a positive net muscle protein balance (MPS > protein breakdown) (1, 2). The anabolic state that occurs in response to protein ingestion either at rest or in recovery from resistance exercise may be indicative of whether or not an individual maintains or accretes muscle mass and strength over time. The magnitude of the anabolic state derived from dietary protein is attributable to the timing of protein ingestion in relation to exercise, as well as to the quantity, source, and quality [i.e., essential amino acid (EAA) content, digestion and absorption kinetics, and subsequent delivery of EAA to peripheral tissue] of the protein consumed (3, 4). Coupling the optimal quantity of post-resistance exercise protein ingestion (0.25-0.30 g/kg and 0.40 g/kg for young and old adults, respectively) with habitual protein intakes between 1.2-2.0 g · kg-1 · day-1 may enhance acute post-resistance exercise MPS and promote favorable adaptive responses to resistance training in healthy young and old adults (5-7). However, the extent to which protein quality modulates the anabolic response to protein ingestion and long-term adaptations to resistance exercise training is not well defined.